GAMBARAN HASIL PEMERIKSAAN SPUTUM PADA PASIEN TB PARU YANG MEROKOK DAN TIDAK MEROKOK DI WILAYAH KERJA PUSKESMAS KAMPUNG DALAM KECAMATAN PONTIANAK TIMUR TAHUN 2012-2013 - ., Tri Juni Ardhi (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Tuberculosis (TB) remains a worldwide public health problem and it isestimated that the global incidence rate will be about 150 per 100000 in 2015. Indonesia ranks fifth in the world that has the largest number of pulmonary TB cases.Tobacco use is among the leading preventable causes of death worldwide, and is amajor contributor to respiratory diseases, including tuberculosis and has long beenunder suspicion for association with the TB epidemic. Object: To investigate thedescription of the examination result on the patients’ sputum with pulmonarytuberculosis who are smokers and non-smokers in the region of Kampung Dalamhealth center, district of east Pontianak in the period 2012-2013. Methods: Thestudy is a descriptive study with cross-sectional design. Results: Description ofsputum smear on the patients’ with pulmonary tuberculosis who are smokers 1+were 15 people (57,69%), 2+ were 5 people (19,23%) and 3+ were 4 people(15,38%). Description of sputum smear on the patients’ who are non-smokers 1+were 24 people (100%). Conclusion: there are variation of sputum positivity on thepatient’ with pulmonary tuberculosis who are smokers. Key words: Sputum Examination, Smoking, Tuberculosis